The Effectiveness Of The Teams Games Tournament (TGT) Cooperative Learning Model Application On Physics Learning Outcomes Of Students - Nadrah, Nadrah (International Journal of Educational Research & Social Sciences, 2023)
The purpose of this study was (1) to find out the physics learning outcomes of students who were taught using the Teams Games Tournament (TGT) cooperative learning model in class XI SMA Negeri 2 Makassar. (2) to find out the physics learning outcomes of students who are taught without using the Teams Games Tournament (TGT) cooperative learning model in class XI SMA Negeri 2 Makassar. (3) to analyze the effectiveness of Teams Games Tournament type cooperative learning model application on the physics learning outcomes of students in class XI SMA Negeri 2 Makassar. This type of research is a quasi-experimental design with nonequivalent control group design using descriptive statistical analysis techniques and inferential statistical analysis. The descriptive research results obtained an average physics learning result in class XI IPA-6 which was taught using the Teams Games Tournament type cooperative learning model of 85.50 and was in the Very Good category, while the average student learning outcomes in class XI IPA-7 taught without using the Teams Games Tournament type cooperative learning model of 79.25 are in the Good category. Based on the results of inferential statistical analysis using hypothesis testing (Independent samples t-test) SPSS data processing obtained Sig = 0.000, it can be concluded that Ho is rejected and H1 is accepted because sig (2-tailet) < α or (0.000 < 0.05 ), thus it can be concluded that there is a significant difference in student physics learning outcomes between classes taught with the Teams Games Tournament (TGT) cooperative learning model and classes taught without the Teams Games Tournament (TGT) cooperative learning model.